2015
DOI: 10.1002/tea.21304
|View full text |Cite
|
Sign up to set email alerts
|

Students' regulation of their emotions in a science classroom

Abstract: Research aimed at understanding the role of the affective domain in student learning in classrooms has undergone a recent resurgence due to the need to understand students' affective response to science instruction. In a case study of a year 8 science class in North Queensland, students worked in small groups to write, film, edit, and produce short videos about the socio-scientific issue of coal seam gas mining as part of a unit on energy. Student emotions over the course of the unit of work were recorded usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 52 publications
7
35
0
6
Order By: Relevance
“…Despite social and cognitive challenges, working in the VLE was perceived very positively by the students and affects, such as joy, interest, and excitement, indicated positive emotional engagement. This result is consistent with Muños et al's study (), in which online game‐play learning in physics was studied and also with Tomas et al's study () of small group work in a science class. Interestingly, all students in the present study reported typically positive affect despite the level of their group outcome.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite social and cognitive challenges, working in the VLE was perceived very positively by the students and affects, such as joy, interest, and excitement, indicated positive emotional engagement. This result is consistent with Muños et al's study (), in which online game‐play learning in physics was studied and also with Tomas et al's study () of small group work in a science class. Interestingly, all students in the present study reported typically positive affect despite the level of their group outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, all students in the present study reported typically positive affect despite the level of their group outcome. This result is in clear contrast with the findings from individual conceptual science learning and mathematics, where positive emotions were related only with high achievement (see Liu et al, ; Wondimu et al, ) but in line with the findings from Newtonian physics studies (Linnenbrink & Pintrich, ) and a socioscientific issue of coal seam gas mining (Tomas et al, ). One plausible explanation could be that the shared experience with peers was considered a positive joint activity, as in Tomas et al's study (), reflecting the positive mood in the groups, which would be consistent with the finding that students reported mostly being happy , relaxed , and calm .…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations